Attention Crisis in Learning: Declining Student Focus in the Digital Distraction Era - Aziizah Kumala Shanti (Journal of Pedagogi, 2026)
The increasing integration of digital technology in education has transformed learning environments but also contributed to an emerging attention crisis among students. The widespread use of smartphones, social media, and online platforms has intensified digital distraction, leading to reduced focus and fragmented cognitive engagement. This study aims to analyze the impact of digital distraction on students’ attention and learning outcomes in contemporary educational settings. The research employs a qualitative approach using a systematic literature review (SLR), drawing on peer-reviewed journal articles and academic sources. Data collection follows structured stages of identification, screening, eligibility, and inclusion, while analysis is conducted through thematic and content analysis to identify patterns related to distraction types, causes, and effects. The findings reveal that multitasking, device-based interruptions, and internal cognitive distractions significantly reduce sustained attention and increase cognitive load, resulting in lower academic performance and superficial learning. Additionally, digital distraction negatively affects classroom interaction and instructional effectiveness. Effective strategies such as attentional literacy, self-regulation, instructional design improvements, and mindfulness-based interventions show potential in mitigating these effects. In conclusion, digital distraction is a major challenge in modern education, requiring integrated and adaptive approaches to enhance student focus and support meaningful learning in the digital era.